Investigation of 3D–Printed Sample Properties for Radiation Physics Applications; Electron, Positron, Neutron and X–ray Scattering under External Influences - Bulavskaya A. A. Angelina Aleksandrovna; Miloichikova I. A. Irina Alekseevna; Polomoshnova D. A. Darjya Anatoljevna; Stuchebrov S. G. Sergey Gennadevich (2025, 2025)
Title screen